EVALUASI PERLAKUAN AKUNTANSI DAN PENERAPAN SAK SYARI’AH UNTUK MEMENUHI KEWAJARAN LAPORAN KEUANGAN ENTITAS SYARI’AH PADA PT. BPR SYARI’AH SPM PAMEKASAN - Syaiful, Syaiful (JURNAL AKUNTANSI DAN INVESTASI, 2017)
The banking sector has a strategic position and is one of the most decisive factors in the development process. Thus, to improve the efficiency and effectiveness of bank functions, the coaching and supervision must be done. Consistency is an essential part of bank management, especially in establishing sound funding strategies, including accounting procedures, in order to stay dynamic in line with the demands of the community as a bank service user. The level of adherence to applicable standards and financial accounting rules can also trigger problems at the level of public confidence, particularly in shari'ah-operated banks against Shari'ah Financial Accounting Standards.  The purpose of this study is to determine the application of Sharia Accounting Standards to transaki-transaction syari'ah and compliance the use of SAK Syari'ah conducted by PT. BPR Syari'ah SPM Pamekasan. This is a descriptive case study research type. The object of research conducted at PT. BPR Syari'ah SPM Pamekasan by looking at data in the form of transactions and financial statements.The results of the analysis of the data obtained and observations made can be seen that the accounting of Islamic banking, both recognition and measurement of transaction journal and presentation of balance sheet and profit and loss made by PT. BPR Syari'ah SPM Pamekasan, so far very relevant and not contrary to the Sharia SAK and operational activities carried out fairly and relevant to the principles of shari'ah.